IDENTIFYING PREFERENCES FOR EVERYDAY LIVING IN HOME HEALTH CARE: RECOMMENDATIONS FROM AN EXPERT PANEL. (16th November 2018) - Sillner, A; Buck, H; Van Haitsma, K; Behrens, L; Abbott, K
Abstract: Research is needed to further understand care preferences in home healthcare where older adults with multiple chronic conditions receive services. The present quality improvement (QI) study convened an expert panel with 16 key stakeholders including home healthcare consumers, direct care providers, and administrators from rural and urban home healthcare settings. The purpose was to determine which items from the Preferences for Everyday Living Inventory (PELI) for nursing home residents were most salient to home healthcare. The PELI is a well-established tool used to assess an individual's preferences in daily personal structure, social and leisure activities, and milieu. Methods included a modified Delphi card sort to 1) rank the PELI categories from most to least important, and 2) select one PELI item from each category most relevant to the setting. Mean scores for ranking of the individual items were calculated. Twelve PELI Items and five PELI categories were identified as having the most salience to to home healthcare. Categories selected as most important were Healthcare Decision Making and Who Delivers Care. Health Care Decision Making continued to be ranked highest (Mean=2.47) across individual stakeholders. Activities of Daily Living (Mean=2.88) and Staff Interactions (Mean=3.13) had the next highest mean scores. Differences in rankings were seen across items and categories based on groups, which may be due to stakeholder roles or regional, cultural, or ethnic differences not apparent in the small convenience sample. Results highlight the potential for incorporating the PELI into home healthcare practice, and the need for additional research.